Analisis Pengaruh Bancassurance dan Tingkat Kecukupan Modal terhadap Profitabilitas Bank Pembangunan Daerah Tahun 2018-2022 - Darapalgia, Ni Komang Maysarah; Eliyanora, Eliyanora; Ahmad, Afridian Wirahadi (Universitas Batanghari Jambi, 2024)
This study aims to determine the effect of bancassurance and capital adequacy ratio on the profitability of Regional Development Banks (BPD) which is proxied in the form of ROA and ROE. This research uses secondary data sourced from the annual financial statements of 26 BPD from all provinces in Indonesia during 2018-2022. The sampling technique uses purposive sampling technique. The data analysis method used is canonical correlation analysis using the SPSS 25 application. The results of the study proved that when tested partially, bancassurance had an effect on ROA, but no effect on ROE, and the Capital Adequacy Ratio had an effect on ROA and ROE. When tested simultaneously, Bancassurance and Capital Adequacy Ratio have an effect on ROA and ROE.